Analisis Peran Bumdes Desa Sukaluyu dalam Meningkatkan Penjualan Melalui UMKM di Desa Sukaluyu - Raihan Haidar Azis; Rieke Retnosary; Dini Yani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
Village-Owned Enterprises (BUMDes) function optimally to increase the village economy, particularly by supporting Micro, Small, and Medium Enterprises (MSMEs). This lesson analyzes of BUMDes Sukaluyu in increasing MSME sales in Sukaluyu Village through financial support, marketing, and business assistance. Descriptive qualitative technique lessons on how to collect reports including interviews, observations, and document analysis. The findings indicate that BUMDes Sukaluyu provides interest-free capital assistance, conducts business training, and facilitates marketing through bazaars and the MSMEs Gallery. However, challenges such as limited capital, lack of digital marketing utilization, and competition from external products still persist. Therefore, enhancing funding sources, digital marketing training, and more effective marketing strategies are necessary for the sustainable growth of (MSMEs).